The Role of Corporate Governance and Risk Management on Banking Financial Performance in Indonesia - Mohamad Bastomi; Ubud Salim; Siti Aisjah (Jurnal Keuangan dan Perbankan, 2017)
This research aimed to examine the effect of corporate governance on financial performance on bank listed on the Indonesia Stock Exchange (IDX) period 2011-2015, either directly or indirectly through credit risk and operational risk. This research used a quantitative approach and the saturated sample method. There were 27 banks that categorized as a sample. Furthermore, Partial Least Square (PLS) used for hypotheses and analysis test and free statistic calculation for Sobel Test version 4 for testing credit risk variables and operational risk as mediation. The results of this research showed that improving the implementation of corporate governance can reduced credit risk and operational risk and increased financial performance, whereas, low credit risk and operational risk can increased financial performance. The results of mediation testing showed that credit risk and operational risk positively mediated the effect of corporate governance on financial performance. This explained that the implementation of good corporate governance can minimize the conflicts of interest and asymmetry information that leads to the cost of non-performing loans and additional capital costs that increased the company profitability.DOI: https://doi.org/10.26905/jkdp.v21i4.1285